Life after lockdown: The experiences of older adults in a contactless digital world - Morrison, Benjamin A.; Nicholson, James; Wood, Becca; Briggs, Pam (Frontiers in Psychology, 2023)
The digital response to the Covid-19 pandemic and its effects on the lives of older adults has been well documented, but less is known about how they experienced the post-lockdown emergence into a relatively contactless digital society. We report the findings from a qualitative survey (n=93) and subsequent interviews (n=9) with older adults aged fifty plus, where they describe their struggles with some of the newly implemented digital interactions, including contactless payments and the use of QR codes and apps to facilitate transactions in cafes, bars and restaurants. A thematic analysis of this data revealed the intrinsic (e.g. digital literacy) and extrinsic (e.g. malfunctioning technology) factors that limited social inclusion for these participants, and that sometimes even led to moments of public humiliation. Our findings shed light on some of the motivational factors that underpin the age-related digital divide, and also highlight the role of self-directed ageism in limiting motivations to learn new digital routines